Respuesta :

Answer:

37

Step-by-step explanation:

Let's use the rule GEMDAS (Grouping, Exponents, Multiply, Divide, Add, Subtract) from left to right. Therefore, we will simplify the equation in the parentheses. [tex]2^{3} = 8. (1-8= -7)[/tex]. -(-7) creates a double negative, deeming the 7 positive, because when there is two negatives the number will turn into a positive. [tex]7^{2}[/tex] = 49, -3 x 4= -12. Therefore the final form of the equation will be 49 - 12 = 37.

Let me know if there are mistakes.

ACCESS MORE